FUNDAMENTALISME GENDER DAN HETERONORMATIVITAS DALAM DUNIA POLITIK - Firnandes, Banokta; Ramlan, Ramlan; Syahrial, Syahrial; Asnizar, Andi; R, Dony.; S, Herman.; Rafli, M.; Fikri, KMS Novyar Satriawan (Bhinneka Multidisiplin Journal, 2025)
In  2016,  the  Italian  Parliament  passed  a  law  that  extended  to  same-sex  couples  most  of  the  rights  of  married  heterosexual  couples. However, the  possibility  of  a  partner  in  a  same-sex  couple  adopting  the  biological  children  of  the  other  partner  so  contro-versial that  it  had  to  be  deleted  in  order  for  the  law  to  pass,  thus  denying  lesbian  and  gay  was  parents  the  legal  protection  they  need.  In  this  article,  we  analyze  the  speeches of  Parliamentarians  who  opposed  the  section  of  the  bill  concerning  lesbian  and  gay  parenthood. The  empirical  analysis  shows  different  discursive  strategies  deployed  by  MPs  to  combat  the  challenges  to  the  heteronormative family,  whose  common  reference  is  the  hegemonic  model  of  gender  which  has  characterized  the  resistance  of  the  Catholic  Church to  the  recognition  of  non-heterosexual  reproduction  and  kinship.  Findings  highlight  that  the  opposition  to  the  recognition  of  gay  and lesbian  parents  contributes  to  reiterating  restrictive  standards  of  motherhood  and  to  maintaining  the  institutionalization  of  sexualities and  reproduction  within  the  patriarchal  order.  Implications  of  the  research  findings  for  public  and  social  policies  are  discussed.